Achievements and Challenges: 30 Years of Housing Reforms in the People's Republic of China - Lu Gao (Asian Development Bank (ADB), 2010)
In the last three decades, the People's Republic of China (PRC) has managed to replace its welfare-based urban housing system with a market-based housing provision scheme. With such significant housing policy changes, the PRC has successfully expanded urban home ownership and impressively increased per capita housing consumption. The housing market has become one of the major pillar industries in the country's economic boom. However, affordable housing development has been greatly lagging behind the ever-increasing housing needs of a large lower-income population in the country, while housing price bubbles cast a shadow on sustainable economic development in the PRC. The main reasons for such challenges include the inefficiency of financial tools to regulate the housing market; and the discrete interests among the central government, local governments, and real estate developers. Within the context of the ongoing global financial crisis, it is even more critical to balance the PRC's housing development, both to address the people's housing needs, and to maintain sustainable growth.
hdl:11540/4184
Keywords: O20; 330; Peoples Republic of China; Housing Policy; Real Estate Reform; Sustainable Economic Development; Wohnungspolitik; Finanzkrise; Wirkungsanalyse; China